THE POTENTIAL OF KARANGANYAR COFFEE PLANTATION TOUR (DE KARANGANJAR KOFFIE PLANTAGE) AS A LOCAL ARRIVAL BASED AGROICITY AREA: (Case Study in Dusun Karanganyar, Modangan Nglegok Village, Blitar Regency) - Fandu Dyangga Pradeta; Andre Kurniawan (JOSAR (Journal of Students Academic Research), 2020)
Blitar is an area that has tourism potential that is potential enough to attract visitors, one of which is the Karanganyar Coffee Plantation Tour in the Modangan village area, Nglegok District, Blitar Regency. This tour just opened around December 2016, with the company name PT Harta Mulia which is managed by Denny Roshadi's family as the sole owner of this plantation around 1940. Researchers are interested in researching this Karanganyar coffee plantation tour, because this tour has a classic European architecture nuance of Dutch buildings that are still preserved by related parties as educational tourism. This tour has the theme of agro-tourism and agrohistory which presents unique characteristics. The purpose of this study was to determine the extent of the coffee plantation tourism potential as an educational tour that still maintains the value of local wisdom. The object of this research is in the village area of ​​Modangan, Nglegok District, Blitar Regency. The subjects of this research are resource persons who are asked for information in accordance with the formulation of the research problem. This study uses a descriptive method through a qualitative approach that directly looks at the conditions and phenomena that exist around the Karanganyar coffee plantation. Data collection methods used were observation, interviews and documentation study. This research explains that Karanganyar coffee plantation has a potential tourism object to be developed with local wisdom values.